An annotated bibliography of theses submitted by MBA/MBM graduates of selected institutions in Metro Manila, 1965-1975 - Manago, Emiliana M.; Picache, Ursula G.; Nortega, Eduardo C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1979)
This special problem aims to provide businessmen, business consultants, students of business and economics, librarians, teachers and other engaged in research and business operation with an annotated bibliography of theses completed by MBA/MBM graduates from seven institutions in Metro Manila during the academic year 1965 through 1975.
Ten institutions were surveyed for the study but only seven were found to have theses in their collections. Two among these institutions do not require their MBA candidates to submit or accomplish a thesis as an end requirement. These are the University of the Philippines and the Pamantasan ng Lungsod ng Maynila. The University of Sto. Tomas Graduate School of Business is new and has not produced any graduate yet. Therefore the schools represented here are: Asian Institute of Management, Ateneo de Manila University, Centro Escolar University Graduate School of Business, Colegio de San Juan de Letran Graduate School of Business, De La Salle University Graduate School of Business, University of the East School of Business, and Far Eastern University Graduate School of Business. Bibliographical sources as well as the library card catalogs of the seven institutions covered in the study were consulted.
A total of nine hundred forty nine (949) theses were identified and listed. Those theses which were not available in the libraries during the time of searching are included in the listing but carry no annotations.
This bibliography is arranged alphabetically by author. Each entry is provided with an item number, from 1 to 949. These are the numbers referred to in the subject index which has been provided to facilitate the location of a specific work.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Business -- Bibliography; Dissertations, Academic -- Bibliography. -- Philippines; Economics -- Bibliography